PEMBUATAN ASAM OKSALAT DARI PELEPAH KELAPA SAWIT (Elaeis guineensis) DENGAN KALSIUM HIDROKSIDA - Iloan Pandang H M; Yos Pawer Ambarita; Seri Maulina (Talenta Publisher (Universitas Sumatera Utara), 2016)
Palm frond is the solid waste which is high in cellulose. Further processing of palm frond is capable of producing high quality product such as oxalic acid. The aim of this research was to obtain the effect of calcium hydroxide (Ca(OH)2) concentration and reaction time on the yield of oxalic acid produced with palm frond as raw material. This study was done with two steps. The first step was the preparation of palm frond until it was ready to be used. The second step was the conversion step which consists of fusion, filtration and crystallization. Oxalic acid produced was then analyzed with quantitative analysis of yield percentage and qualitative analysis using Fourier Transform Infra Red (FTIR) spectroscopy and plat melting point apparatus. The result showed that the maximum yield of oxalic acid was achieved at Ca(OH)2 concentration of 3.5 N and reaction time of 60 minutes, the value was 6.07 % based on weight of palm frond. The qualitative analysis showed that the vibration of functional groups had approached the standard oxalic acid with the melting point was 106.2 oC.